Nilai-Nilai Ilahiah dalam Hukum di Indonesia - Aziz, Fathul Aminudin (Al-Manahij: Jurnal Kajian Hukum Islam, 2010)
Intellectual honesty represent significant spiritual value that has been reserved by the people in Indonesia. Mean while, there are many religions and some societies exploit the variety of those interpretations.